Synthesis of organic silane microcapsules for self-healing corrosion resistant polymer coatings - Huang, Mingxing (2013)
Hydrolysable organic silane, i.e. 1H,1H,2H,2H-perfluorooctyl triethoxysilane (POTS), was carefully selected and microencapsulated as healing agent via in situ polymerization in an oil-in-water emulsion. The microcapsule size was adjustable via changing agitation rate for various coating systems. POTS microcapsules were incorporated into epoxy resin and coated on a steel substrate to form a corrosion resistant organic coating. The corrosion test in the salt solution demonstrated the good corrosion resistance of the self-healing coating compared to the control sample. Additional analysis revealed that the corrosion prohibition functionality was realised by an autonomous self-healing mechanism of the encapsulated POTS hydrolysed with water upon scratch.